APLIKASI KEWIRASWASTAAN BAGI MAHASISWA - Nina Septina (Bina Ekonomi, 2000)
Entrepreneurship is not a new concept. An entrepreneur is a person that has a high morality, sensitive to his / her environment and possesses an entrepreneur mentality and entrepreneurial skill. Therefore entrepreneurship is not only applied by businessperson but also by everyone in his / her daily life. This paper discusses an application of the entrepreneurship aspects in student’s life. Some examples will be given for illustration